Lupus - Ali Khan, Wahid (IntechOpen, 2017)
Lupus is a new book that will serve as perfect update to lupus for all those who are studying/working at different levels starting from graduate students up to senior investigators. This book provides a comprehensive guide to the latest issues and new developments in the field of lupus. The contents are based on different authors extensive research experience in lupus whether for basic or clinical specialties. Divided into four sections, each one covers the basic concept that will be equally valuable both for the expert and for those who are beginners in this field.